Determinan Kemiskinan di DI Yogyakarta Tahun 2011-2020 - Ahmad Irsyad Agung; Winih Budiarti (Politeknik Statistika STIS, 2022)
Poverty is one of the factors to see the welfare of the people in an area. One indicator to see poverty in an area is the percentage value of poverty. In 2020, in the publication of the Central Statistics Agency, DI Yogyakarta is the province with the highest poverty percentage value of all provinces on the island of Java and is above the national poverty. If the problem of poverty in Yogyakarta is not immediately addressed, the people who are trapped in poverty will always be in a cycle of poverty. This study aims to explain the determinants of poverty in DI Yogyakarta in 2011-2020. The type of data used is panel data with a cross-section of 5 provinces from 2011-2020. By using panel data regression analysis with fixed effect mode, the results show that the variables of life expectancy (UHH), economic growth rate (LPE) and minimum wage have a significant negative effect, while literacy rate (AMH) does not have a significant effect on the percentage of poverty in Indonesia. DI Yogyakarta Province in 2011-2020.